Distribution of selected invasive plant species in the Romensko-Poltavsky Geobotanical District (Ukraine) - Dvirna, Tetyana S. (Biodiversity: Research and Conservation, 2016)
The paper presents the distribution of 10 selected invasive plant species in Ukraine. The studied taxa comprised 8 invasive and 2 potentially invasive species. All species were characterized in phytogeographical, biological and ecological terms. Their distribution was shown on grid maps.